2018
DOI: 10.4103/apjon.apjon_6_18
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Oncology Unit Nurse Managers on Missed Nursing Care: A Qualitative Study

Abstract: Objective:The main objective of this study was to explore factors affecting missed nursing care in oncology units from the perspective of nurse managers.Methods:Twenty nurse managers working at oncology units of referral teaching hospitals in Iran participated in this study. Data were collected through individual face-to-face and telephonic interviews using an interview guide. Focus groups were also conducted. Data were analyzed using conventional content analysis.Results:System structure, underlying factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 27 publications
5
66
0
4
Order By: Relevance
“…Of the studies reviewed, only two papers specifically placed emphasis on nurse managers' or nurse leaders' roles in relation to influencing missed care, Dehghan-Nayeri et al (2018) and Kalisch and Lee (2012). Furthermore, these were the only studies to present the perspectives of nurse managers' or nurse leaders' themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies reviewed, only two papers specifically placed emphasis on nurse managers' or nurse leaders' roles in relation to influencing missed care, Dehghan-Nayeri et al (2018) and Kalisch and Lee (2012). Furthermore, these were the only studies to present the perspectives of nurse managers' or nurse leaders' themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Ambiguity around roles and responsibilities was evident in some studies. Strained relationships between NMs and staff nurses were noted as a barrier to reporting missed care (Dehghan-Nayeri et al, 2015;Dehghan-Nayeri, Shali, Navabi, & Ghaffari, 2018;Papastavrou et al, 2014). Nurses reported that they often have different care priorities to NMs and explained that managers frequently question their decisions and request they change their care plans (Papastavrou et al, 2014).…”
Section: Values and Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a poor work setting, where the nurse manager has no information about implicit nursing care rationing or has information but no leadership skills, nurses may be dissatisfied with the workplace environment (Dehghan-Nayeri, Shali, Navabi, & Ghaffari, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the article, perspectives of oncology unit nurse managers on missed nursing care: A qualitative study,[1] My heart goes out to my global nursing family who are represented in this article. I want them to know, they are not alone!…”
mentioning
confidence: 99%